(untitled) (World Marxist Review, 2026)
The theory of "new-quality productive forces" proposed by General Secretary Xi Jinping represents a new leap forward in the Marxist theory on productive forces. Since its founding, the Communist Party of China (CPC) has always represented the development trend of China's advanced productive forces and taken the liberation and development of the productive forces as its fundamental mission. During the New Democratic Revolution, the CPC focused on "liberating the constrained productive forces" as the goal of the revolution. In the period of socialist revolution and construction, it emphasized "protecting and developing the productive forces under the new relations of production." In the new period of reform, opening up, and socialist modernization, it put forward the proposition that "science and technology are the primary productive forces." In the new era of socialism with Chinese characteristics, it has set forth the strategic task of accelerating the development of "new-quality productive forces." The CPC's basic experience in developing advanced productive forces can be summarized as follows: First, adhering to the Party's overall leadership in the development of advanced productive forces. Second, regarding the liberation and development of productive forces as the essential requirement and fundamental mission of socialism. Third, realizing the unity of productive forces and relations of production by resolving the principal contradictions of society. Fourth, adhering to the comprehensive deepening of reform to form relations of production compatible with productive forces. Fifth, forging a path of independent innovation with Chinese characteristics on the basis of self-reliance. These valuable historical experiences provide important guidance for the current development of new-quality productive forces.